Global Strategies: Navigating the Complexities of International Business in a Connected World - Hasanah, Lila (Advances in Business & Industrial Marketing Research, 2024)
This research investigates the dynamics of global strategies in the context of contemporary international business. The purpose is to identify emerging trends, challenges, and opportunities in the global business landscape and provide insights for practitioners, policymakers, and academics. A qualitative research methodology is employed, involving a systematic review of relevant literature from academic journals, books, and online databases. Thematic analysis and narrative synthesis are used to examine key themes and patterns in the literature. The findings reveal significant trends such as digital globalization, sustainability, and geopolitical dynamics, which are reshaping the international business environment.The discussion highlights the implications of these trends for firms, including the need for strategic agility, cross-cultural competence, and sustainability integration. The study underscores the importance of adapting global strategies to navigate uncertainty and capitalize on emerging opportunities in a rapidly changing world.